No Decline in the Risk of Stroke Following Incident Atrial Fibrillation Since 2000 in the Community: A Concerning Trend - Alanna M. Chamberlain; Robert D. Brown; Alvaro Alonso; Bernard J. Gersh; Jill M. Killian; Susan A. Weston; Véronique L. Roger (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2016)
BackgroundWhile atrial fibrillation is a recognized risk factor for stroke, contemporary data on trends in stroke incidence after the diagnosis of atrial fibrillation are scarce. Methods and ResultsOlmsted County, MN residents with incident atrial fibrillation or atrial flutter (collectively referred to as AF) from 2000 to 2010 were identified. Cox regression determined associations of year of AF diagnosis with ischemic stroke and transient ischemic attack (TIA) occurring through 2013. Among 3247 AF patients, 321 (10%) had an ischemic stroke/TIA over a mean of 4.6 years (incidence rate [95% CI] per 100 person‐years: 2.14 [1.91–2.38]). Two hundred thirty‐nine (7%) of 3265 AF patients experienced an ischemic stroke (incidence rate: 1.54 [1.35–1.75]). The risk of both outcomes remained unchanged over time after adjusting for demographics and comorbidities (hazard ratio [95% CI] per year of AF diagnosis: 1.00 [0.96–1.04] for ischemic stroke/TIA; 1.01 [0.96–1.06] for ischemic stroke only). In analyses restricted to patients with prescription information, the rates of anticoagulation use did not change over time, reaching 50.8% at 1 year after AF diagnosis. Further adjustment for anticoagulation use did not alter the temporal trends in stroke incidence (hazard ratio [95% CI] per year of AF diagnosis: 1.06 [0.97–1.15] for ischemic stroke/TIA; 1.08 [0.98–1.20] for ischemic stroke only). ConclusionsStrokes/TIAs are frequent after AF, occurring in 10% of patients after 5 years of follow‐up. The occurrence of stroke/TIA did not decline over the last decade, which may be influenced by a leveling off of anticoagulation use. This concerning trend has major public health implications.